Synergistic antitumor activity of baicalein combined with almonertinib in almonertinib-resistant non-small cell lung cancer cells through the reactive oxygen species-mediated PI3K/Akt pathway - Chen, Teng; Zhang, Pei; Cong, Xiao-Fan; Wang, Yuan-Yuan; Li, Shuo; Wang, Hao; Zhao, Su-Rong; Sun, Xiao-Jin (Frontiers in Pharmacology, 2024)
Almonertinib, an important third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), exhibits high selectivity to EGFR-sensitizing and T790M resistance mutations. Nevertheless, almonertinib resistance is a major obstacle in clinical use. Baicalein, possessing antitumor property, but the mechanism of its anti-tumor action against almonertinib-resistant non-small cell lung cancer (NSCLC) remains yet unelucidated. In the current study, we intended to evaluate the effect of baicalein and/or almonertinib on proliferation, apoptosis, and associated pathways in almonertinib-resistant NSCLC HCC827/AR and H1975/AR cells. The findings presented that baicalein or almonertinib repressed cell viability of HCC827/AR and H1975/AR cells concentrationdependently. The combined application of the two drugs dramatically attenuated the cell proliferation, triggered apoptosis, caused the cleavage of Caspase-3, PARP, and Caspase-9, and significantly inhibited the tumor growth in nude mice. Furthermore, based upon the findings of network pharmacology study, it was found that baicalein combined with almonertinib led to a massive accumulation of ROS, and pre-incubation with N-acetyl-L-cysteine (ROS remover) prevented the proliferation inhibition and apoptosis induction by combination treatment, and partially recovered the decline of p-Akt andp-PI3K, highlighting the crucial role of ROS in apoptosis and PI3K/Akt pathway. In conclusion, these findings implied that baicalein combined with almonertinib improved antitumor activity in almonertinib-resistant NSCLC through ROS-mediated PI3K/Akt pathway.